TECHNOLOGIES FOR THE PROCESSING OF NUTRITIOUS RESIDUES - Томчук, Василь (Modern engineering and innovative technologies, 2022)
The article investigates practical application of modern technologies for the use of crop residues as organic fertilizers and mulch. The mechanisms of conversion of straw into organic fertilizer are identified. Methods of mulching in tillage are describe